(untitled) (Conferencea, 2023)
This article is intended for technical students and provides information on the methodology of using web technologies to organize independent education. The research proves that the use of web-based technologies can increase the effectiveness of science teaching and improve the academic performance of students inside and outside the classroom. It is known from experience that introducing the practice of using web technologies for independent thinking and creative work among pedagogues and students is one of the important tasks. Technical students offer valuable insights into the potential benefits of using web technologies to facilitate the management of independent learning organizations.